Data Set--Choice-Based Revenue Management: Data from a Major Hotel Chain - Bodea, Tudor; Ferguson, Mark; Garrow, Laurie (Manufacturing & service operations management, 2009)
In this paper, we describe data collected from five U.S. properties of a major hotel chain that can be used to benchmark the performance of choice-based revenue management (RM) algorithms. The process used to collect this data illustrates subtle complexities involved in extracting product availability information from current RM systems and sheds new light on practical issues that need to be addressed to successfully implement choice-based RM systems. The data described in this paper is publicly available at the journal's website at http://msom.pubs.informs.org .